Public key cryptography - PKC 2011 14th international conference on practice and theory of public key cryptography, Taormina, Italy, March 6-9, 2011 : proceedings - Catalano, Dario (Lecture notes in computer science, 2011)
This book constitutes the thoroughly refereed proceedings of the 14th International Conference on Practice and Theory in Public Key Cryptography, PKC 2011, held in Taormina, Italy, in March 2011. The 28 papers presented were carefully reviewed and selected from 103 submissions. The book also contains one invited talk. The papers are grouped in topical sections on signatures, attribute based encryption, number theory, protocols, chosen-ciphertext security, encryption, zero-knowledge, and cryptanalysis.